The Impact of Organizational Culture on Employee Productivity - Temiloluwa Olakunle (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
The success of a company and the efficiency of its employees are both influenced by its culture. The purpose of this research was to examine the link between company culture and productivity, with an eye toward determining which variables moderate or mediate this connection. A poll questionnaire was used to gather information from a representative cross-section of workers across several sectors. The group was analyzed using descriptive statistics, and the connection between company culture and productivity was investigated using multiple regression. The analysis's findings point to a positive correlation between company culture and output, suggesting that happy workers tend to produce better results. Leadership style, communication, and employee involvement were all identified as potential moderators of this connection. These results have significant ramifications for business owners and managers who want to foster a productive and effective workplace environment. Organizations can foster employee engagement and dedication by giving attention to the creation of a positive atmosphere that places value on teamwork, communication, and employee empowerment. The result could be increased productivity and general success. The findings of this research stress the value of a positive company culture in fostering good performance. Important insights into the factors that may moderate or mediate the relationship between organizational culture and employee productivity are provided by the research results, which highlight the importance of organizations prioritizing the development of a positive workplace culture.